Persepsi Guru Terhadap Pembelajaran Tematik pada Masa Pandemi Covid-19 di SD Negeri 1 Muktisari - Faranita, Faranita; Misdalina, Misdalina; Hera, Treny (Institut Teknologi Pendidikan Indonesia, 2022)
This researcher aims to describe teachers' perceptions of thematic learning during theCOVID-19 pandemic at SD Negeri 1 Muktisari. This study uses descriptive qualitative research methods, namely the data collected in the form of words, pictures, and not numbers. The data can come from interview scripts and documentation. The informants of this research are high grade teachers IV, V and V. The results of the research are as follows: (1) teachers are quite good in delivering thematic learning online (2) in delivering learning materials online the difficulties experienced by students are learning media such as mobile phones android, internet quota, which is not sufficient. Meanwhile, teachers do not experience difficulties during the learning process (3) in the assessment process teachers still havedifficulties because they cannot assess directly. Before the learning process, the teacher prepares lesson plans, teaching materials, student books and learning media in the form of videos or audio that have been made to master the learning materials.